Response of bermudagrass to enhanced-efficiency fertilizers, application strategies and release under tropical conditions - Borges, Bernardo Melo Montes Nogueira [UNESP] (2020)
Nitrogen fertilization is an important input for crop yield; however, it can result in detrimental environmental effects due to low use efficiency of regular N sources. This study evaluated the effects of N fertilizers and application strategies (single vs. split application) on bermudagrass (Cynodon spp.) responses and release pattern and rate in controlled and field incubations. The bermudagrass study was arranged in a two-way factorial scheme of 6 N fertilizers, urea, Polymer Coated Urea (PCU), PCU-6 (6 months), PCU-4 (4 months), PCU-2 (2 months) and urea + urease inhibitor (U-NBPT) applied as a single (400 kg N ha-1 yr-1) or two split applications of 200 kg N ha-1 (400 kg N ha-1 yr-1). The controlled experiment was a two-way factorial of PCU-6, PCU-4, PCU-2 and 15, 45 and 90% water hold capacity (WHC), sampling period of 170 days, the field incubation used the same sources sampled up to 220 days. Enhanced-efficiency fertilizers (EEF) increased herbage accumulation (HA) by 1.3 Mg ha-1 compared to untreated urea, on average. Nitrogen use efficiency (NUE) was greater for EEFs (44%) than urea (36%). Results showed that increased soil moisture inferred positive responses in release pattern and a minimum of 45% WHC was necessary for optimum release. Fertilizers at field conditions resulted in an earlier release than expected, ~20 days.